2018
DOI: 10.2147/phmt.s165933
|View full text |Cite
|
Sign up to set email alerts
|

Iodine deficiency and its associated factors among primary school children in Anchar district, Eastern Ethiopia

Abstract: BackgroundIodine deficiency is a major public health problem in Ethiopia. Most of the studies in Ethiopia were done on clinical goiter without assessing the subclinical iodine deficiency. Therefore, there was a need to study the magnitude and associated factors of iodine deficiency among school-age children in Eastern Ethiopia.Subjects and methodsA school-based cross-sectional study design was used to assess the iodine level of 200 primary school children aged 6–12 years who were selected by using the multista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…The median urinary iodine level in this study was 158.5 μg/L ranging from 5.1 μg/L to 528.8 μg/L which is higher than a study in Bahir Dar, Amhara region Ethiopia and Aira district, west Ethiopia that showed a median urinary iodine level of 58.8 mg/L (12.89 mg/L to 564.5 mg/L) [14] and 70.5 μg/l respectively [15]. Another study in Anchar district, Eastern Ethiopia, reported a median urinary iodine concentration of 146 μg/L which is comparable with the present study.…”
Section: Discussioncontrasting
confidence: 77%
“…The median urinary iodine level in this study was 158.5 μg/L ranging from 5.1 μg/L to 528.8 μg/L which is higher than a study in Bahir Dar, Amhara region Ethiopia and Aira district, west Ethiopia that showed a median urinary iodine level of 58.8 mg/L (12.89 mg/L to 564.5 mg/L) [14] and 70.5 μg/l respectively [15]. Another study in Anchar district, Eastern Ethiopia, reported a median urinary iodine concentration of 146 μg/L which is comparable with the present study.…”
Section: Discussioncontrasting
confidence: 77%
“…Similarly, a study in pregnant women in Tanzania reported that the poorest households were associated with a higher prevalence of iodine deficiency (24) . In addition, Muktar et al reported that the poorest households in Ethiopia were associated with iodine deficiency in school children (25) . In Peru, Tarqui-Mamani et al found that households with extreme poverty and poverty had the highest consumption of salt with inadequate iodine concentrations (11) .…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is not statistically signi cant, the pooled effect size of sex of the children was 1.87, which was obtained from ve studies [31][32][33][34]36]. Accordingly, the odds of becoming Iodine de cient is nearly 2 (OR: 1.87, 95% CI: 1.43-2.44) times higher among female school children compared to male school children (Fig.…”
Section: Association Of Sex With Iodine De Ciencymentioning
confidence: 94%
“…Association of goiterogenic food consumption and iodine de ciency was examined by using two studies [33,36] and found that the odds of iodine de ciency among school aged children is nearly 3 (OR: 2.93, 95% CI: 1.60: 5.35) times higher among children who had ever consumed goiterogenic foods compared to those who had never consumed them (Fig. 8).…”
Section: Association Of Goiterogenic Food Consumption With Iodine De ...mentioning
confidence: 99%